Ameloblastic fibroma - Božič, Marko (Radiology and oncology (Ljubljana), 2006)
Background. Ameloblastic fibroma (AF) is a rare odontogenic tumour. It consists of odontogenic ectomesenchyme resembling the dental papilla and epithelium resembling dental lamina and enamel organ without dental hard tissues. Case report. A case report of a large ameloblastic fibroma involving the body of mandible from the lower Icff second incisor (32) to the lower leftsecond molar (37) is presented. To our knowledge this is the only case of ameloblastic fibroma reported from Slovenia. Conclusions. An aggressive surgical treatment is suggested because of the possibility of recurrence and the possibility of malignant transformation of an AF to an ameloblastic fibrosarcoma.
Keywords: Adult; Fibrom; Fibroma; mandibula; Mandibular Neoplasms; Mandibularne novotvorbe; novotvorbe; Odontom; Odontoma; Odrasli; tumor